A Escola de Ensino Médio Casa Familiar Rural de Frederico Westphalen - RS e a produção e reprodução local e regional a partir dos seus egressos: um estudo de caso - Lourenzi, Lucinéia (2015)
This paper deals with research about the contributions of High School Rural Family House located in the city of Frederico Westphalen-RS, for the production and social reproduction of the municipality and region, the main actors of this research the young graduates of this institution, which is the main objective of this work. Is justified by the need to diagnose through its graduates unless the latter educator whose adopted teaching methodology is the Pedagogy of Alternation, meets or not your aim to provide an education with full and social, whose principles are grounded in the pursuit of recovery and maintenance activities that guarantee sustainable production and social reproduction replaced over time efficient tools for more economically. The choice of approach with the main actors the young graduates, as well as provided a challenge, a great stimulus to investigate the design, practice and outcomes of work-linked training, as it is believed that the Education Field and the Pedagogy of Alternation are important alternatives for the preservation and maintenance of rural peasant activities in Brazil, in this case particularly the study area. To better understand the reality involving the studied subjects, we chose to use is a qualitative research, understanding that the construction of this science is a social phenomenon. This study sought to answer very specific questions and worries about the level of reality that can not only be quantified, we sought to explore a universe of knowledge, meanings and experiences.